Stomach Content Analysis of Fish Living Around Floating Net Cage Aquaculture in The Koto Panjang Dam, Kampar Regency, Riau Province - Tumanggor, Josua Setiawan; Windarti, Windarti; Eddiwan, Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Fish feed pellets that enter the water around the floating net cage may affects the feeding habit of wild fish living around the cage. To understand the stomach content of fish living around the floating net cage in the Koto Panjang Dam, a study has been conducted on  December 2018.  Samplings were conducted 3 times, once/ 2 weeks and the fish were captured using   gill net and lure, in the surface up to 15 m depth. Stomach content of the fish was then analyzed and identified. Were 9 fish species present. The remains of fish feed pellets were present in the stomach of all fishes captured and the percentage of fish pellets in the stomach of the fish were as follows:   15% in the Puntius schwanefeldii; 67% in Hampala bimaculata; 25% in Tynnichtys vaillanti ;  83% in  Puntius bramoides ;   23% in Macrones nigriceps; 25% in Mastacembelus unicolor; 50% in Osphronemus goramy; 67% in Cyprinus carpio and100%  in Oreochromis niloticus. High portion of fish feed pellets in the stomach of several wild fish species indicates that the wild fishes are greatly affected by the presence of fish feed pellets remains, while the presence of the pellets in the stomach of M. unicolor and M. nigriceps indicates that the remain of the pellets also affects the fish that live in   15 m depth.  Keywords: Pellets, feeding habit, floating net, stomach content, Koto Panjang Reservoir